Evaluation of Competence Certification for The Prospective Graduates of Institut Pemerintahan Dalam Negeri Year 2020-2022 (Jurnal MSDA (Manajemen Sumber Daya Aparatur), 2023)
The Institute of Home Affairs Governance (IPDN) has been conducting competency certification for prospective graduates since 2020. However, one of the major issues encountered was the lack of accreditation and coordination with the National Agency of Profession Certification (BNSP) or a Professional Certification Institute (LSP). Therefore, it is crucial to evaluate the implementation of competency certification for prospective IPDN graduates from 2020 to 2022. This study assessed the context, input, process, and product aspects of the certification process using an evaluative approach using the CIPP model and quantitative descriptive methods. Data were collected through questionnaires, interviews, and documentation analysis. The analysis utilized the CIPP evaluation model, which encompassed the context, input, process, and product dimensions. The findings indicate that the overall evaluation of the implementation of competency certification for prospective IPDN graduates from 2020 to 2022 falls under the non-conforming criteria. Specifically, the context dimension is strongly appropriate, while the input and process dimensions are deemed not Appropriate, and the product dimension is strongly inappropriate. It is important to note that the implementation of competency certification for prospective IPDN graduates in this period lacks legal validity as it does not align with BNSP coordination. To address these issues, it is recommended that IPDN promptly establishes an LSP as a BNSP-certified educational institution and enhances the competence and number of BNSP-licensed assessors based on the specific needs of each Study Program. In the meantime, competency certification for prospective IPDN graduates can be conducted through a selection system. ABSTRAK Institut Pemerintahan Dalam Negeri (IPDN) telah melaksanakan sertifikasi kompetensi bagi calon lulusannya sejak Year 2020. Salah satu permasalahan yang muncul adalah pelaksanaan sertifikasi kompetensi tidak dilaksanakan dan tidak terakreditasi oleh Badan Nasional Sertifikasi Profesi (BNSP) atau Lembaga Serifikasi Profesi (LSP). Untuk itu perlu dilakukan evaluasi pelaksanaan sertifikasi kompetensi bagi calon lulusan IPDN Year 2020-2022. Tujuan penelitian ini adalah untuk mengevaluasi pelaksanaan sertifikasi kompetensi bagi calon lulusan IPDN, dari aspek konteks, aspek input, aspek proses, dan aspek produk. Penelitian ini merupakan penelitian evaluatif dengan menggunakan model CIPP dengan pendekatan deskriptif kuantitatif. Teknik pengumpulan data menggunakan teknik angket, wawancara, dan dokumentasi. Alat analisis menggunakan model evaluasi CIPP yang meliputi aspek Konteks, Input, Proses, dan Produk. Hasil penelitian menunjukkan bahwa evaluasi pelaksanaan sertifikasi kompetensi bagi calon lulusan IPDN Year 2020-2022 dengan menggunakan model CIPP, secara umum berada pada kriteria Inappropriate, dengan rincian kriteria pada Dimensi Konteks Very Appropriate, Dimensi Input dan Dimensi Proses Inappropriate, serta Dimensi Produk Very Inappropriate. Dari sisi regulasi, pelaksanaan sertifikasi kompetensi bagi calon lulusan IPDN Year 2020-2022 tidak memperoleh legalitas karena mulai proses pelaksanaan sampai dengan produk yang dihasilkan tidak melakukan koordinasi dengan BNSP. Rekomendasi kebijakan yang disarankan, yaitu IPDN segera membentuk Lembaga Sertifikasi Profesi (LSP) seperti LSP pihak kesatu lembaga Pendidikan bersertifikasi BNSP serta meningkatkan kompetensi dan jumlah asesor yang terlisensi BNSP berdasarkan kebutuhan masing-masing Study Program. Pelaksanaan sertifikasi kompetensi bagi calon lulusan IPDN dapat dilakukan melalui sistem seleksi yang transparan dan terbuka sehingga hanya yang lulus seleksi yang dapat mengikuti sertifikasi kompetensi.